Hati-Hati dengan Berita Konspirasi: Studi Pengaruh Terpapar Berita Konspirasi COVID-19 terhadap Persepsi Risiko dan Kepatuhan terhadap Protokol Kesehatan - Nuri Sadida; Fathiyah Faiha Faisal (Jurnal Ilmiah Psikologi MIND SET, 2021)
Until 2021, the COVID-19 epidemic has shown no indications of fading in Indonesia. On the other hand, there is a growing amount of talk on social media concerning COVID-19 being a hoax. The distribution of information regarding COVID-19 as a conspiracy is considered to have weakened public perceptions of risk and cooperation with health regulations, potentially delaying the end of the pandemic in Indonesia. As a result, the goal of this study was to determine the impact of COVID-19 news exposure on risk perception and adherence to health protocols. This study used an experimental research approach that was carried out via online media. A total of 112 people were recruited as participants, all of them were young adults. The findings of this study show that participants who were exposed to news of the COVID-19 conspiracy, i.e., those in the experimental group, had a lower risk perception than those who were not exposed to news of the COVID-19 conspiracy or those in the control group (U=1997.5, P=.011). Furthermore, risk perception has a substantial favorable link with adherence to health procedures, according to this study. This indicates that someone who has heard of the COVID-19 conspiracy has a lower risk perception, and that someone with a lower risk perception is less likely to follow health protocols. The essay goes into greater detail on the implications and limitations.